International consequences of the activation of Title III of the Helms Burton Act - Jalil, Carlos (Riga Graduate School of Law, 2020)
In May 2019 the U.S. government activated the Title III of the Helms Burton Act. Title III grants U.S. nationals whose property was expropriated in Cuba after the 1959 revolution a private right of action against those who traffic in their property. The purpose of the thesis is to analyze the legal, political, economic and social consequences of the activation and its incompatibility with international law. The study therefore examines expropriation rights, state immunity from jurisdiction and the extraterritorial application of U.S. laws. Analytical and applied legal research has been conducted by evaluating primary and secondary sources of law such as national legislation, treaties, international jurisprudence and legal opinions. Such sources are applied in lawsuits against companies including Meliá, Expedia and Booking that use property expropriated from U.S. nationals. The main findings reveal that Title III property claims will have jurisdictional problems in national courts because expropriation disputes are intergovernmental. The thesis, however, not only demonstrates that the Helms Burton Act aggravates Cuba’s economic crisis and undermines international law, but also proposes possible approaches for resolving property claims.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; State immunity; United States of America